Development Of A Remotely Piloted Airship System For Monitoring And Tracking Wildlife In The Woodland - Ishak, Nurul Hidayah (Universiti Sains Malaysia, 2017)
Previously, the surveying and monitoring were done using existing ground-based techniques, for example camera traps installation in the hot spot areas and footprint observation which are potentially imprecise and fallacious and difficult to verify. Besides, surveying threatened and is invasive towards the species making efforts protect the population becoming more challenging as it requires a substantial amount of time and resources invested in the project. After years of studies, the experts came out with UAVs innovation ideas for monitoring and tracking, hence this project is another study for the UAV to implement this technique for that very purpose. The primary objective of this project is to develop a proof of concept for the Unmanned Aerial Vehicle (UAV) flight platform. This project deals with the control of lighter-than-air aircraft which is a non-rigid airship otherwise known as blimp, more specifically focusing on the design of the embedded hardware and software built onto the airship. This system was developed to monitor and track the wildlife in the woodland. UAVs were chosen because it can potentially increase the results accuracy, is human-risk free, and a cheaper platform of aerial surveys. The challenge for this project was the development of the control flight system and also the navigation and communication control system for the airship. The objective required extended knowledge of electronics and mechanical propulsion. This project was done according to the subsystems which complement the main airship system. The design for the components performance were done up prior to selecting the right components to serve its purpose. Moreover, an electronics system for unmanned flight was designed and built onto the gondola. Then, the systems were integrated as one complete system. In order to verify the effectiveness of the control system, several tests were done once the system was fully integrated. The purpose of the tests was to observe the performance of the system before going forward with the flight test. The tests were done at different conditions of the performance. Moreover, for the communication system, the experiments were carried out in order to receive video in real time of the subjects to accomplish the objectives. The purpose was to see how effective and feasible the system would be in order to proceed with the mission.